(untitled) (Historia, 2021)
It seems possible that many of the findings made in research are serendipitous. The chance publication of a paper or book or a conversation overheard in a lift or passageway may have an enormous effect in changing the direction of someone in the midst of a research endeavour. For example the chance meeting of the authors of this research paper could never have been foreseen. Neither of them was aware of the other before their serendipitous encounter. This act of pure happenstance led to clarification of certain problem areas in the story of Joan Bax (1637-1678), Governor of the Cape of Good Hope. If Laing and Goris had not had this 'serendipitous' meeting this analysis would never have been done. The research digresses into the period of the Eighty Years war and the involvement of the Bax family during this era. Research was done on three levels - heraldic, historical and genealogical. The authors brought together different strengths in a 'synergistic' manner, which tries to find an answer to this enigmatic figure in Cape history. It is strange that this Cape Governor was destined to enter the history books as Bax 'entitled Van Herentals.' This paper hopes to show that the so-called Herentals connection is very dubious. End